(untitled) (Journal of Industrial and Mechanical Engineering, 2020)
The contribution of the SME sector to La Matanza export development has played a key role since the studies on foreign trade and export promotion link country export development with economic growth. Therefore, it is important to measure the export performance of a country or region. In the case of the La Matanza´s SME, its performance will be analyzed based on the data collected during the 2009-2014 period. Likewise, the dynamism of international markets will be examined for the main export products and markets where the share of exports is significant. This will make it possible to identify the region’s main challenges when it comes to promoting the growth and diversification of exports for the promotion of their economic development.